Digitally deconstructing a pícaro: examining the role of the Digital Humanities in the L2 learning and teaching of Lazarillo de Tormes - Johnston, Kelsie (Kansas State University, 2020)
This paper addresses different digital strategies taken from an L2 perspective in the analysis of the classic picaresque novel, Lazarillo de Tormes (1554). I combine the strengths of two digital humanities tools in order to better bridge the cultural divide that may stand between the L2 learner and the narrative’s pícaro. This study aims to blend the use of LIWC, a digital sentiment analysis tool, with Storymap, a digital mapping software from Knightlab, in order to create a robust linguistic, historic and geographic analysis. The combination of software platforms will quantify and display the emotional associations that Lázaro, the protagonist of the novel, expresses towards each physical landmark he mentions. This analysis aims to reveal the strategies used in the first-person narrative to tie emotions, either positive or negative, to each specific location mentioned in central Spain. By plotting each place that appears in the narrative and reviewing the data of the sentiment analysis, my project is designed to better understand why the protagonist is so specific when mentioning, sites, towns, and cities both in Spain and abroad. This study effectively blends Digital Humanities tools and traditional literary analyses in order to show how the inclusion of advanced technologies in the L2 classroom has the potential to unlock cultural, historical and geographical information hidden in the target culture’s literature.
Keywords: Second language literature; Digital humanities; Lazarillo de Tormes; Storymap; Google Maps